The Effect of Audit Fee, Audit Rotation, and Auditor Reputation on Audit Quality - Nursiam Nursiam; Febry Krisna Putri; Pardi Pardi (Riset Akuntansi dan Keuangan Indonesia, 2021)
The purpose of this research is to examine the effect of audit fee, audit rotation, and auditor reputation to audit quality. The population in this study is manufacturing companies listed on the BEI period 2014-2018. Total sample of research is 345 companies determined by purposive sampling. Data analysis was done by logistic regression and SPSS Statistic 20. The result of this study show that audit fee have no effect on audit quality, while audit rotation and auditor reputation has significant effect on audit quality.